Identification of diagnostic KASP-SNP markers for routine breeding activities in yam (Dioscorea spp.) - Agre, A.P.; Clark, L.V.; Garcia-Oliveira, A.L.; Bohar, R.; Adebola, P.O.; Asiedu, R.; Terauchi, R.; Asfaw, A. (Wiley, 2024)
Maintaining genetic purity and true-to-type clone identification are important action steps in breeding programs. This study aimed to develop a universal set of kompetitive allele-specific polymerase chain reaction (KASP)-based single nucleotide polymorphism (SNP) markers for routine breeding activities. Ultra-low-density SNP markers were created using an initial set of 173,675 SNPs that were obtained from whole-genome resequencing of 333 diverse white Guinea yam (Dioscorea rotundata Poir) genotypes. From whole-genome resequencing data, 99 putative SNP markers were found and successfully converted to high-throughput KASP genotyping assays. The markers set was validated on 374 genotypes representing six yam species. Out of the 99 markers, 50 were highly polymorphic across the species and could distinguish different yam species and pedigree origins. The selected SNP markers classified the validation population based on the different yam species and identified potential duplicates within yam species. Through penalized analysis, the male parent of progenies involved in polycrosses was successfully predicted and validated. Our research was a trailblazer in validating KASP-based SNP assays for species identification, parental fingerprinting, and quality control (QC) and quality assurance (QA) in yam breeding programs.